Estudio de factibilidad para la creación de una granja cunícola en la sabana de Bogotá (2018)
The present feasibility study is carried out in order to implement a rabbit farm where the breeding, fattening, raising and slaughtering of rabbits and subsequent distribution takes place, in the municipality of Chia, Sabana Norte of Bogotá D.C. Studies were developed which, according to their development, allowed us to interpret with possibilities of demand for the product even though this is very new for our society, but satisfying the needs of the market. An area was adapted in the outskirts of chia with pertinent characteristics to install cages and special rooms for the development of the productive process, additional to adapt zones for the crop of forages and tubers that are going to be the food of the animals and to contribute to the self sustainability from the farm. Taking into account all the Colombian regulations for the perfect development of our legal and organizational activity, always taking into account the welfare of our workers and people who are part of our company. The project is completed with a financial analysis which, according to results, indicates the feasibility, profitability and viability of the study carried out.